Comparison of Maximum Angles of Knee Varus and Flexion in the Stance Phase of Walking on a Treadmill with Different Inclinations between Female Athletes with Genu Valgum and Healthy Knees - Katayoon Gilani; Fariborz Mohammadipour; Mohammadreza Amirseyfaddini (Vesnu Publications, 2020)
Introduction: The use of treadmills and sports equipment is on the rise due to long stay at home because of the progression of Coronavirus Disease (COVID-19), and hence, tendency of individuals to exercise at home. Common movement patterns in non-contact anterior cruciate ligament (ACL) injuries include decreased knee flexion accompanied by increased knee valgus angles. Therefore, the aim of this study is to investigate the maximum angles of knee varus and flexion when walking on positive, negative, and zero treadmill inclinations.Materials and Methods: 29 subjects within the age range of 18-28 years were selected and divided into two groups of healthy (weight: 58.95 ± 8.58, height: 163.14 ± 3.95, intermalleolar distance: 0.46 ± 0.40) and genu valgum (weight: 61.60 ± 5.56, height: 161.80 ± 5.50, intermalleolar distance: 6.95 ± 2.51). The parameters of maximum angles of knee varus and flexion when walking on -10, zero, +10% treadmill inclinations were calculated using three-dimensional motion analysis system. The data were processed in Cortex and MATLAB softwares and analyzed using mixed repeated measure at the significant level of P < 0.050.Results: The results of this study showed that the highest values of maximum angles of knee varus and flexion were observed at -10% inclination. In addition, the maximum varus angle did not differ significantly between the positive and zero inclinations, but the maximum flexion angle showed a significant difference between these two inclinations.Conclusion: Since walking on negative inclinations inclines the knee angle in the frontal plane toward the varus and increases the flexion angle and decreases the load exerted on the ACL, this type of walking can be more effective in rehabilitating people with genu valgum.